O aconselhamento linguageiro como forma de intervenção e formação docente - NONATO, Rejane Santos (Universidade Federal do Pará, 2015)
This research aims at finding ways to improve the in-service training of English teachers from countryside public schools of Pará State. In order to do so, I use the language advising (LA) which is a form of language support that through conversations, aims at promoting selfdirected learning (GARDNER; MILLER, 1999; MOZZON-McPHERSON, 2007; RILEY, 1997; VIEIRA, 2007). I base myself on Vygotsky (1984) studies, which discuss human development and knowledge construction; Benson (2001), which deals with the process of autonomization, and Mozzon-McPherson (2001), which is about language advising. The research methodology belongs to the qualitative research method since it is an action research. The sequence of procedures was nested in the project coordinated by Magno e Silva (2013), in which firstly, the advisee’s personal experience of learning the FL was analyzed and an area of personal preoccupation was identified; then it was planned proactively targeting the area of personal preoccupation, the third step was to exert a monitored intervention, and finally, as a last step, it was done the evaluation and the replanning. To carry out this research it was used as instruments of data collection learning narratives, needs analysis questionnaire, reports of advising sessions. Subsequently, the data obtained through these instruments were organized and analyzed in the light of the theory raised. The results indicated that the LA can help in the formation of teachers in practice favoring the development of autonomy of these professionals, once the advising period allowed teachers reflect on their language knowledge, their beliefs, difficulties and strategies to overcome these difficulties, leading these teachers to perform actions in search of their linguistic and professional development.